Frequency of Suicide Ideation and Attempt in HIV infected patients referred to behavioral health counseling center of Rafsanjan (RUMS) and Kerman University of medical sciences (KUMS) in 2012: - Bidaki, Reza; Soltani, Hossein; Zolala, Hossein; Sayadi Anari, Ahmadreza; Asadi, Razie; Shafee, Ali; Riahy, Ali; Asadpour, Mohammad; Salehi Shahrbabaki, Mohammad Hossein; Sabouri Ghannad, Masoud; et al. (Galen Medical Journal, 2015)
Background: Suicidal behavior and HIV/AIDS are considered as significant public health concerns. HIV infection has been associated with elevated risk of suicidal ideation. Methods and Materials: Cross-sectional and descriptive research design was used to record socio-demographic data of the study. The suicidal ideation scale BECK was used to determine and measure the frequency of suicide ideation and attempt in HIV infected (HIV+) persons referred to behavioral health counseling center of Rafsanjan University of medical sciences (RUMS) and Kerman University of medical sciences (KUMS) in 2012. Results: Men had more suicidal ideation than women after the diagnosis of infection with HIV. More cases of HIV positive persons with duration of less than 10 and more than 14 years, and most cases of less than 40 years-old had suicidal ideation. There was no significant difference between suicidal ideation in HIV-infected individuals and factors such as gender, age, and duration of HIV-infection (p >0.05). Conclusion: Suicidal ideation and attempt is common in HIV infected patients which needs more assessment and prevention.